Combined effects of plant based fungicides and arbuscular mycorrhizal fungi on corn - Md Jaafar @ Ahmad Jaafar, Noraini; Khor, J. J. L. (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Current awareness to minimize the farmer’s dependency and application of chemical fungicide has brought natural fungicide into perspective as an environmental-friendly measure. Wood vinegar (WV) and plant extract, such as soursop leaf extract (SE) are proven to be an effective natural fungicide. The bioactive compounds in natural fungicides were proven to kill the fungal pathogen damaging plants seeds and growth. However, little is known on the combined effects of natural fungicide with beneficial soil microorganisms such as arbuscular mycorrhizal fungi (AMF) on plants. Hence, the objective of this study was to evaluate the effects of natural fungicides and AMF and growth of sweet corn (Zea mays). Nine fungicide treatments and 2 AMF treatments (with and without AMF inoculation) with 4 replications were used in this experiment. The treatments consisted of T1 as control (without natural fungicide), T2 (WV 5%), T3 (WV 10%), T4 (WV 15%), T5 (WV 20%), T6 (SE 0.5%), T7 (SE 1%), T8 (SE 1.5%), and T9 (SE 2%). The natural fungicide was applied 11 days after transplanting and plants were harvested at 40 days after transplanting. Wood vinegar (WV) did not affect plant growth significantly, but soursop leaf extract at 1.5% and 2% significantly decreased corn growth and inhibited AMF. In conclusion, natural fungicide when in combination with AMF, should be applied at lower concentrations to ensure AMF infectivity and effectiveness in improving plant growth performance and nutrient uptake. Soursop leaf extract (SE) at 1.5% concentration could be used as effective fungicide, but higher concentration would exert negative effects towards beneficial soil fungi (in this case the AMF), hence reducing plant growth performance.